Natural phytosanitary products effects on Bacillus thuringiensis subsp. kurstaki (Berliner) - Everton Ricardi Lozano da Silva (Semina: Ciências Agrárias, 2012)
This work aimed to evaluate the effect of natural phytossanitary products (NPP) on spores and crystal toxicity of Bacillus thuringiensis subsp. kurstaki – HD1 (Btk). For this commercial products (Agromos, Biogermex, Bovemax, Bordeaux mixture, Ecolife®, Dalneen, Matan Plus, Pyronin and Stüble-Aid®) were used at three different concentrations. The effect of NPP on spores was assessed by comparing a suspension of Btk + NPP with sterile distilled water (SDW) and another suspension with nutrient broth (NB), inoculated on nutrient agar (NA) in Petri dishes to quantify the number of CFU/mL, 18 h after inoculation and incubation. The effect of NPP on crystals was evaluated with a suspension of Btk+SDW+NPP added to the arti¿cial diet supplied for Anticarsia gemmatalis Hub. (Lepidoptera: Noctuidae) quantifying the number of dead larvae at 12, 24, 48 and 72 h. Matan Plus was the only natural product that did not present effect on spores. All other products, regardless of concentration, decreased signi¿cantly CFU/mL. Regarding crystals, Bordeaux mixture was the only one that reduced signi¿cantly Btk insecticidal activity at three concentrations.